Penerapan Algoritma Decision Tree untuk Prediksi Tekanan Udara di Stasiun Meteorologi Cengkareng - Fariyani; Djuniadi; Sunarno; Iqbal (AI Society & STMIK Indonesia, 2025)
Meteorology is a science that studies the movement of wind, clouds and water vapor with a main focus on weather prediction. Air pressure is one of the important meteorological parameters that can provide an initial indication of weather changes. Air pressure is used as a reference for taking off and landing aircraft at the airport. The variables needed to predict air pressure include air pressure, wind direction, temperature, wind speed and air humidity. The aim of this research is to predict air pressure at the Cengkareng Meteorological Station using the Decision Tree Algorithm and RapidMiner software. The data in this research comes from BMKGSoft for the period 2019 – 2023. BMKGSoft is used to track data sent from the station to the database server. The research results show that the prediction of air pressure at the Cengkareng Meteorological Station using the decision tree algorithm is very good with RMSE values: 0.208 +/- 0.000, MAE: 0.046 +/- 0.203, squared error: 0.043 +/- 2.967 and squared correlation: 0.987.